Prognosticating First Trimester Vaginal Bleeding: A Case-Control Study Of Obstetric Outcome In A Tertiary Care Center - Kyalakond, Keerti; Kaur, Gagandeep; Srivastava, Saumya; H Karegowda, Lakshmikanth; Mittal, Harramb (Journal of Neonatal Surgery, 2025)
Aims And Objectives: To evaluate the impact of first-trimester vaginal bleeding as a predictor of adverse pregnancy outcomes. Material And Methods: A case-control study was conducted for a year, comprising of 80 cases and controls. The cases and controls were followed up and obstetric outcomes were noted which includes missed/complete/incomplete abortion, preterm delivery, premature rupture of membrane (PROM), preterm premature rupture of membrane (PPROM), IUGR, manual removal of placenta, preeclampsia, abruption placenta, placenta previa were tabulated and statistical analysis performed. Results: Incidence of first trimester vaginal bleeding was 18-20%. Overall, subjects with first trimester bleeding had statistically significant higher risk of preterm delivery [8.75% vs. 1.25%;OR-7.57;P value:0.030], PROM [15% vs. 5%;OR-3.53;P value:0.035], PPROM [8.75% vs. 1.25%;OR-7.57;P value:0.03], abortion [20% vs. 2.5% ;OR- 8.75;P value:0.002]. IUGR [3.75% vs. 2.5%;OR-1.52], pre-eclampsia [5% vs. 2.5%;OR- 2.05], abruption placenta [2.5% vs 1.25%;OR-2.03], manual removal of placenta [5% vs.1.25%;OR-4.15] were not statistically significant. Similarly there was no statistically significant difference in the cesarean section (47.6% vs 47.7%) and vaginal delivery (50.8% vs 52% ) in both groups.All babies had normal APGAR. Conclusion: In the present study, 80% of the subjects continued their pregnancy despite having had threatened abortion in the first trimester. It was found that there was an increased risk of preterm delivery, PROM, PPROM , and abortion which was significant.